(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article investigates linguistic creativity of one of the brightest representatives of Ukrainian journalism and aphoristic - Alexander Perlyuk who masterfully manipulated by various linguistic means, it demonstrates not only their creativity, but also its own individual style. Attention is drawn to the fact that the problem linguistic creativity is directly related to the language game, which is the basis of a large number of aphoristic phrasing. Aphorisms are treated as such, in the form of games are relevant to modern society realities, especially the problem of corruption in the government and officials, the poverty of the general population and social inequality, economic instability and unemployment, personal choice, allocation of labor resources, the totalitarian legacy of democracy, formation civil society, interpersonal relationships, and so on. The precedent statements are identified that illustrate the wide variety of authors’ experiment with language material. We investigate one of the most popular methods of creating comic effect - pun. It turns out that most of the proposed aphorism-perlyukizms are based on paradox, which is provided by various means. Special attention focuses on repetition, antithesis, enantiosemy, oxymoron, paraphrasing, parceling.